EVALUATION OF NON FAT SOLIDS SUBSTITUTES (NSL) IN A HARD DAIRY ICE CREAM MIX WITH VEGETABLE FAT - LÓPEZ M.Sc., Francy; SEPÚLVEDA V. M.Sc., José U. (Vitae, 2012)
Background: In industries that produce ice cream, NFMS required in the mixture are obtained by addition of skim milk powder and whole milk, condensed milk, caseinate and others. However, due to factors such as national lack of these (caseinates) and the seasonal climate of regions which produce milk, these raw materials are relatively expensive, so it has increased the interest of using different substituents of non-fat milk solids (NFMS) without affecting the nutritional and sensory quality of ice cream, which comply with national legislation and represent a lower price to make them. Objectives: This study aimed to implement and evaluate a NFMS formulation for applying in ice cream mixes. Methods: the formulation (F1 substitute), was applied at different rates (20, 40, 60%) in mixtures of ice cream and was compared to a control without replacement. The physicochemical properties that were investigated included the mix viscosity, acidity, ph, mineral content (calcium and phosphorus), protein, ash, fat and total solids. In the ice cream was determined freezing, melting, overrun, whipping ability and sensory evaluation. For the study of the data was used Statgraphics 5.0 and the experimental design was a randomized complete block model with multiple range test of Duncan. Results: The results show that the viscosity value of the treatment, varies in a range of 398.7 to 1108.6 cp at a temperature of 4 °C, being higher for T4 (higher percentage of substitution). The titratable acidity values of the ice cream mixture ranged from 0.17% to 0.12% with a higher (P <0.05) for T1. The protein content ranged from 3.2% to 2.5%. Conclusions: As the percentage of non-fat milk solids replacement increases, the protein percentage and melting decrease, reaching values established by Colombian law. With this study it is concluded that, the 40% substitution of non fat milk solids over ice cream mixture, is the one with the best physicochemical and sensory characteristics.